Energy saving in a gas processing plant through application of a membrane system - Saidi, Hamdani; Che Yunus, Azizi (Faculty of Chemical & Natural Resources Engineering, 1989)
Malaysia is rapidly emerging as a Newly Industrialized Countries (NIC). This shows the rapid pace of industrial programmes currently going on in the country. Even though energy resources in the form of petroleum deposit and hydropower are easily available, it is not too early at this present stage to monitor the energy requirements in industries and develop an efficient energy conservation approach so as to maximize these energy resources. This paper is intended to estimate the energy requirement in a Gas Processing Plant (GPP) having processing capacity of 250 MMSCFD natural gas and to estimate the energy saving that can be generated through the utilization of a Gas Membrane Separation System.